Bangladesh Skills for Tomorrow’s Jobs : Preparing Youth for a Fast-Changing Economy - World Bank (World Bank, Washington, DC, 2018)
The skills for tomorrow’s Jobs in Bangladesh attempts to address key skills challenges and identifyopportunities in the backdrop of fast technological and economic changes. It proposes mid to long-term strategic policy options that would contribute to economic growth and job creation in Bangladesh with a focus on post-secondary education and skills development sectors. It aims to inform the Government and the World Bank’s jobs agenda. The study draws upon relevant literatures from international and national sources, the government’s surveys and education statistics, and analytical works undertaken by the World Bank and other agencies. Moreover, the study was extensively informed and guided by knowledge and insights gathered through the experience from the World Bank funded operations and series of consultations on skills for future jobs with relevant stakeholders in Bangladesh.